ELT Student Teachers’ attitudes towards Teaching Profession - Tütüniş, Birsen; Yalman, Duygu (My University, 2018)
This paper present the results of the research on the student teachers‘ attitudes towards their profession conducted at English Language Teaching Department of a Turkish university. In Turkey students are enrolled in universities in accordance with their grade obtained for university entrance exam designed by the Higher Education Council. Some students who have a good command of English enroll in English Teacher Education program (ETE). However, they do not always want to become English teachers. Language proficiency is the only reason for enrolling in that program. This choice has a great impact on their attitude towards their profession. Attitude is defined as a relatively enduring organization of beliefs, feelings and behavioral tendencies towards socially significant objects, groups, events or symbols1. Attitude is an umbrella term for beliefs, feelings, and behavioral tendencies. Recent studies in the field of teacher education have focused on exploring teachers‘ beliefs2. Teachers‘ beliefs play a central role in teachers‘ decision making, their judgments, and behavior3,4,5. Previous studies identified the importance of teachers‘ beliefs in understanding the effectiveness of language teaching and learning6, and has contributed to drawing implications for teacher training7,8. Our study is aimed to identify ELT student teachers‘ attitudes towards English Language Teaching. We conducted a mixed method research combining an attitude survey, which consists of 34 items, and semi-structured interviews9. The survey focused on future teachers‘ beliefs, feelings, and behavioral tendencies. 44 third- and fourth-year ELT students participated in the research.
Keywords: attitude; ELT; student teacher; FLTEP